Saman and Atas Nama Cinta in the View of Canonisation of Literature - Suyitno, Suyitno (ASPENSI in Bandung, Indonesia, 2017)
ABSTRACT: The polemic of literary legitimation within Indonesian literature in the era of Reformation is triggered by Saut Situmorang (2007)âs essay on âPolitik Kanonisasi Sastraâ (Politic of Literary Canonisation). The essay has triggered a debate within the field of Indonesian literature, and has received considerable responses from literary critics and the man/woman of letters. This paper questions the legitimacies of Ayu Utamiâs novel of âSamanâ and of Denny Januar Aliâs a prose-poetry of âAtas Nama Cintaâ (In the Name of Love). The ongoing debate within Indonesian literature is discussed in the discourse of the canonisation of literature and its relation to theory of hegemony and counter-hegemony. However, some man/woman of letters were worried about Hans-Georg Gadamer (1990)âs thesis on the creation of presupposition and perception built on the exposition of historical situatedness. This paper also identifies the existence of oligarchic power relations between the literary agents in the legitimation of Indonesian literary worksâ quality. There is bias in the mentioned legitimation and the literary community has collusioned to legitimize this literary work. Proper to mention here is the rivalry between KUK (Komunitas Utan Kayu or Utan Kayu Community) and BP (Boemi Poetera or Indigenous). The former is led by Goenawan Mohamad and the later is under the influence of Saut Situmorang.KEY WORDS: Literary Canonisation; Hegemony; Counter-Hegemony; Literary Legitimacy; Historical Situatedness.About the Author: Dr. Suyitno is a Lecturer at the Study Program of Indonesian Language and Literature Education, Department of Language and Arts Education FKIP UNS (Faculty of Education and Teacher Training, State University of Surakarta), Jalan Ir. Sutami No.36-A, Kentingan, Jebres, Kota Surakarta 57126, Central Java, Indonesia. His contact e-mail is: yitsuyitno52@gmail.comRecommended Citation: Suyitno. (2017). âSaman and Atas Nama Cinta in the View of Canonisation of Literatureâ in TAWARIKH: International Journal for Historical Studies, Vol.9(1), October, pp.81-94. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Article Timeline: Accepted (November 15, 2016); Revised (March 20, 2017); and Published (October 28, 2017).